An activatable AIEgen probe for in-situ monitoring and long-term tracking of ferrous ions in living cells. (June 2021) - Yang, Liu; Chen, Qingxin; Gan, Shenglong; Guo, Qiang; Zhang, Jie; Zhang, Huatang; Xie, Yusheng; Xiao, Hanyue; Wang, Wanhe; Sun, Hongyan
Abstract: Homeostasis of iron ions takes part in a number of biological processes. Its dysregulation is associated with various diseases. However, the lack of effective fluorescent probe for detecting ferrous ion (Fe 2+ ) severely hinders our in-depth understanding of its biological functions. Herein, the aggregation induced emission (AIE)-based probe QM-Fe for Fe 2+ detection was reported. The probe demonstrated intriguing photophysical properties including near infrared emission, large Stokes shift as well as AIE characteristics. In aqueous solution, the probe also displayed rapid response, high sensitivity, and high selectivity towards Fe 2+ . More importantly, QM-Fe demonstrated great ability to detect endogenous and exogenous Fe 2+ in living cells, showing superior property over the aggregation caused quenching (ACQ) probe DCM-Fe owing to in-situ monitoring and long-term tracking ability. We envision that this work will provide a solid basis for the development of next-generation Fe 2+ fluorescent probes. Highlights: An AIE fluorescent probe QM-Fe for Fe 2+ detection was reported. The probe displays prominent properties including fast response, large Stokes shift and NIR emission. This probe was successfully utilized to visualize exogenous and endogenous Fe 2+ in HepG2 cells. The AIE probe demonstrates priority to ACQ probe in in-situ monitoring and long-term tracking of Fe 2+ .